Pengaruh Iklim Keselamatan dan Pengalaman Personal terhadap Kepatuhan pada Peraturan Keselamatan Pekerja konstruksi - - Prihatiningsih; - Sugiyanto (Faculty of Psychology, Universitas Gadjah Mada, 2010)
This study was conducted to examine the effect of safety climate and personal experience on safety compliance, particularly in the use of personal protective equipment (PPE), of construction workers. Safety climate and compliance questionnaire was used to measure the level of safety climate and compliance. Personal experience variable consist of work experience and educational experience that was analyzed independently as two variables. The subject of this study (N=70) are construction workers in the rehabilitation project of Amongrogo, in Yogyakarta. Multiple regressions is used for data analyzing. The result indicate the significant effect of both safety climate and personal experience toward safety compliance, particularly in the use of PPE (R 2= .253; p<.05). The coefficient of determination is .253 indicating that both safety climate and personal experience result together 25.3% effective contribution for safety compliance. Safety climate itself results 7.8%, while personal experience results 17.5% effective contribution for safety compliance. There are only three dimensions of safety climate, from sixth dimensions being examined, that have significant effect to safety compliance, which are supervisor safety practices, safety attitude, and safety training dimension. Supervisor safety practices have dominant effect, and result 39.8% effective contribution on safety compliance.